Responding to stakeholder needs to engage rehabilitation professionals in the delivery of evidence-based health programming for adults with osteoarthritis - Chevan, Julia; Barrett, Maureen; Nowakowski, Kimberly; Pappas, Kathleen; Murphy, Heather; Erck, Elizabeth; Weisner, Serena (Frontiers in Rehabilitation Sciences, 2022)
Although there are many evidence-based programs that promote healthy lifestyles and symptom modification for people with osteoarthritis, their delivery in rehabilitation clinical settings in the United States is limited. These programs can be a primary component of treatment or a discharge option to facilitate long-term mobility and pain management. The purpose of this perspective article is to describe a delivery model that brings one arthritis-appropriate, evidence-based intervention, the Arthritis Foundation’s Walk With Ease program, to older adults seeking physical therapy related to their osteoarthritis. We embedded program delivery into a Doctor of Physical Therapy curriculum using a student health coaching approach and partnering with physical therapy clinics and other community agencies for participant referrals. This model of delivery is cost-effective, sustainable, and provides outcomes that meet goals of the national agenda for osteoarthritis. The model provides benefits for students in health professions education programs, community organizations and rehabilitation clinics, and adults living with osteoarthritis.